2020
DOI: 10.3389/fonc.2020.581814
|View full text |Cite|
|
Sign up to set email alerts
|

Mifepristone as a Potential Therapy to Reduce Angiogenesis and P-Glycoprotein Associated With Glioblastoma Resistance to Temozolomide

Abstract: Glioblastoma, the most common primary central nervous system tumor, is characterized by extensive vascular neoformation and an area of necrosis generated by rapid proliferation. The standard treatment for this type of tumor is surgery followed by chemotherapy based on temozolomide and radiotherapy, resulting in poor patient survival. Glioblastoma is known for strong resistance to treatment, frequent recurrence and rapid progression. The aim of this study was to evaluate whether mifepristone, an antihormonal ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Multivariate logistic regression analysis showed that age, cystic tumor degeneration, degree of edema around the tumor, and uneven internal echogenicity of the tumor were independent risk factors for high-grade glioma, which indicated that the older the patient was and the more severe the degree of peritumoral edema, the greater the probability of high-grade glioma. These results are partly consistent with the findings obtained by MRI (22), and they may relate to the growth pattern of high-grade gliomas, which grow rapidly and have an insufficient blood supply, leading to necrosis of the emergent tissues (23). Also, highgrade glioma's growth process often leads to the destruction of the blood-brain barrier and an increase in vascular permeability (24), causing edema in the surrounding brain tissue.…”
Section: Discussionsupporting
confidence: 83%
“…Multivariate logistic regression analysis showed that age, cystic tumor degeneration, degree of edema around the tumor, and uneven internal echogenicity of the tumor were independent risk factors for high-grade glioma, which indicated that the older the patient was and the more severe the degree of peritumoral edema, the greater the probability of high-grade glioma. These results are partly consistent with the findings obtained by MRI (22), and they may relate to the growth pattern of high-grade gliomas, which grow rapidly and have an insufficient blood supply, leading to necrosis of the emergent tissues (23). Also, highgrade glioma's growth process often leads to the destruction of the blood-brain barrier and an increase in vascular permeability (24), causing edema in the surrounding brain tissue.…”
Section: Discussionsupporting
confidence: 83%
“…The tumor growth rate was slower than that found with temozolomide alone, indicating a chemo-sensitizing effect. According to the current results, mifepristone could contribute to the modulation of tumor relapse in glioblastoma by decreasing the levels of VEGF, MGMT, and P-gp ( 34 ). Further research is needed to explore other mechanisms of drug resistance of glioblastoma tumors.…”
Section: Introductionmentioning
confidence: 60%
“…As a result, these proteins have become an important therapeutic target to improve patient response to glioblastoma treatment. As we have mentioned, several studies reported that mifepristone decreased MGMT and P-gp expression ( 33 , 34 ) ( Figure 2 ). Future research is required to determine whether mifepristone can regulate glioma stem cells, offer greater benefits during tumor recurrence and improve the prognosis of patients with glioma.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations